Pemanfaatan Media Visual untuk Meningkatkan Hasil Belajar Siswa Kelas V pada Mata Pelajaran IPAS di SD Inpres Leleko - Deysti Tarusu; Nofry V. Wongkar (Journal on Education, 2024)
This research was conducted with the aim of determining the influence of the use of visual media to improve student learning outcomes in science and social subjects, specially in food chain materials in elementary schools. Library research is a type of research used. The data collection technique is carried out by collecting scientific journals that are considered relevant to the existing research variables, namely visual media, learning outcomes, and food chain science and technology materials. The data presented has been processed and analyzed to be concise and systematic. The results of the research that have been reviewed are based on previous research that is considered relevant to the variables studied, regarding the use of visual media to improve student learning outcomes in science subjects in elementary schools. Visual media has an impact on improving the learning outcomes of class V students studying science at SD Inpres Leleko, according to the analysis thats was done.